Urban art, politics and memory in 2019: First steps toward the creation of an archive of political muralism in Santiago de Chile - Molina Loyola, Mauricio Eduardo (2020)
This essay was born from the concern about the volatility of graffiti as a work, image and intervention of urban space and seeks to be an exploration of what happens with mural graffiti in Santiago, Chile. It focuses on the political vocation of the latter considering as important precedents the Mexican muralism as well as the Ramona Parra and Elmo Catalán Brigades. The work emphasizes muralism with a political vocation and explicit messages leading them to what has been understood as the social role of art from authors such as Nelly Richard or Gaspar Galaz, referring to the work of graffiti artists such as Agotok, UFO or Aguarda Kiltro with important interventions in the southern area of ​​Santiago, a sector characterized by the popular habitat. At the methodological level, an exploration is carried out on Santa Rosa Avenue, one of the main arteries of the southern area of ​​Santiago, with a large number of works on its walls, concluding in the cultural center where the work “the goal of Chile” is located of the prominent muralist Roberto Matta. Emphasis is placed on the need for a photographic record of urban art, in order to form a properly organized fund for the conformation of an archive of urban art that would be a highly dynamic and constantly disputed field, being an interesting exercise to recover and strengthen the social historical memory. In conclusion, it is highlighted that this outline is presented as a first step, a reflective exercise on the need to register and file as a memory exercise that can result in outstanding experiences. Emphasis is placed on the need for a photographic record of urban art, in order to form a suitably ordered fund to create an archive of urban art that would be a highly dynamic and constantly disputed field, an interesting exercise to recover and strengthen the historical social memory. Finally, a long-term but highly relevant work is proposed around the creation of an archive of urban art with explicit political messages in Santiago, with the hard work involved.